Perspektif Islam Tentang Tradisi Lokal dalam Proses Pelaksanaan Upacara Beati di Gorontalo - Mokoginta, Sandri (Prodi Pendidikan Agama Islam IAINU Kebumen, 2022)
Religion and culture are two important things in society that influence each other. When religious teachings enter a cultured community, there will be a tug of war between cultural interests on the other side. Likewise with the Islamic religion which was passed down in the midst of Arab society which has customs and traditions passed down from generation to generation. The patterns adopted by Islam in responding to Arab customs during the process of forming Islamic law can also be used as a guide in adapting adat to Islamic law elsewhere. Even though Islamic law is in a fixed form, it does not mean that Islamic law refuses flexibility in dealing with the customs and habits of a place. Tradition is part of culture. One of the local traditions that is closely attached to the life of Indonesian people, especially Gorontalo, is the process of carrying out the beati ceremony. The beati traditional ceremony in Gorontalo society is carried out after going through several stages such as molongudu, momonto, momuhuto, mopohuta'a to pingge, mome'ati and mohatam. In other words, before the beati ceremony as the main ceremony is carried out, it is preceded by the ceremonies of molongudu, momonto, momuhuto, mopohuta'a to pingge, momeati and mohatamu. This series of ceremonies is part of the beati ceremony. Furthermore, the customary stakeholders will mopom'lumu (confirm) that the entire series of events has been completed, and ends with mongabi. That is an indicationthat the event can be disbanded. At that time, the audience immediately stood up and dispersed while saying sholawat to the Prophet SAW. accompanied by a handshake.